DAMPAK GAME ONLINE MOBILE LEGENDS TERHADAP PERILAKU REMAJA USIA 17-21 TAHUN DI DESA SEKURA KABUPATEN SAMBAS - Hanisa, Hanisa; Mukhlis, Mukhlis; Gaffar, Zakiah Hasan; Marini, Marini; Musa, Pabali; Nurwijayanto, Nurwijayanto (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This study aims to provide understanding to the community, especially teenagers in Sekura Village regarding the negative impacts of the Mobile Legends online game so that they can reduce their playing hours so as not to cause addiction that results in them. This research was conducted using a descriptive method with a qualitative approach, the determination of informants was carried out using the purposive sampling method, namely adolescents aged 17-21 years who were addicted to online games and parents of these adolescents. The results of this study show that there is a phenomenon of online game addiction that occurs in Sekura Village and is mostly experienced by mid-to-late adolescent adolescents, because at that age it is very vulnerable to the impact of online games due to their immature minds and still want to play a lot. The causative factors of online game addiction are boredom so looking for more fun things, following friends and lack of supervision from parents. The negative impact of Mobile Legends game addiction results in teenagers wasting their time on things that are not useful, often and easily speak abusive or negative language, health that is not maintained properly, and ignore the people around them